Analisis Faktor-Faktor Kesulitan Pembelajaran Online Mata Kuliah Biokimia di Masa Pandemi COVID-19 - afrahamiryano afrahamiryano (Eduscience Development Journal, 2020)
The distance learning system implemented by all universities during the Covid-19 pandemic has a number of challenges for lecturers and students. This article describes empirically the application of online learning in the Biochemistry course, Biology Education study program, Mahaputra Muhammad Yamin University. This pandemic has brought a paradigm shift in learning, namely developing and empowering various media in the learning environment, one of which is the internet facility. The results showed that the use of the internet as a learning medium in general was able to increase student learning motivation in taking Biochemistry courses, but on the other hand it created a dilemma where students had difficulty understanding concepts. This is due to the limited means of supporting the learning process such as textbooks. Difficulties are also experienced by lecturers, this difficulty creates a pleasant learning atmosphere in the midst of limited facilities and learning facilities and infrastructure.